Eccentric exercise and delayed onset muscle soreness of the quadriceps induce adjustments in agonist–antagonist activity, which are dependent on the motor task - Vila-Chã, Carolina (2012)
This study investigates the effects of eccentric exercise and delayed onset muscle soreness (DOMS) of the quadriceps on agonist–antagonist activity during a range of motor tasks. Ten healthy volunteers (age, mean ± SD, 24.9 ± 3.2 years) performed maximum voluntary contractions (MVC) and explosive isometric contractions of the knee extensors followed by isometric contractions at 2.5, 5, 10, 15, 20, and 30% MVC at baseline, immediately after and 24 h after eccentric exercise of the quadriceps. During each task, force of the knee extensors and surface EMG of the vasti and hamstrings muscles were recorded concurrently. Rate of force development (RFD) was computed from the explosive isometric contraction, and the coefficient of variation of the force (CoV) signal was estimated from the submaximal contractions. Twenty-four hours after exercise, the subjects rated their perceived pain intensity as 4.1 ± 1.2 (score out of 10). The maximum RFD and MVC of the knee extensors was reduced immediately post- and 24 h after eccentric exercise compared to baseline (average across both time points: 19.1 ± 17.1% and 11.9 ± 9.8% lower, respectively, P\0.05). The CoV for force during the submaximal contractions was greater immediately after eccentric exercise (up to 66% higher than baseline, P\0.001) and remained higher 24 h postexercise during the presence of DOMS (P\0.01). For the explosive and MVC tasks, the EMG amplitude of the vasti muscles decreased immediately after exercise and was accompanied by increased antagonist EMG for the explosive contraction only. On the contrary, reduced force steadiness was accompanied by a general increase in EMG amplitude of the vasti muscles and was accompanied by increased antagonist activity, but only at higher force levels ([15% MVC). This study shows that eccentric exercise and subsequent DOMS of the quadriceps reduce the maximal force, rate of force development and force steadiness of the knee extensors, and is accompanied by different